Modern aspects of electrochemistry - Vayenas, Costas G. ; White, Ralph E. ; Gamboa-Aldeco, Maria E. (Springer, 2017)
The volume is unique both in the selection of topics, which cover key issues of engineering electrochemical technologies, and in the quality of the authors which include at least five international leaders on their area of expertise